Perancangan dan Penerapan Basis Data pada Aplikasi Penjualan di Toko Graha Komputer Kebumen - Fahmi Fachri; Jaka Dernata (Journal of Cyber Health and Computer, 2024)
The development of increasingly sophisticated technology allows the process of activities to run very fast. The presence of technology makes work within the company easier and stays abreast of advances in the business world. Ordering or purchasing systems from suppliers that are stored as stock and sales to monthly reports at Graha Komputer Kebumen after a long period of not using a computerized system or recording manually will cause problems that arise in the sales process. This study aims to design and build a desktop-based cashier application for the sale of computer parts at the Graha Komputer Kebumen store which aims to provide convenience in managing offices related to buying and selling computer parts. So that it can make store management easier and make it more neat and structured. By using the SDLC method described in ERD which implements a database that is accessed using Microsoft Access and desktop-based applications, it is deemed able to meet the needs of store management. (Abstract) Keywords—component; Implementation, SDLC, ERD